Bourdieu's Theory of the State : A Critical Introduction - Loyal, Steven (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book critically examines Pierre Bourdieu's theory of the state by assessing its theoretical and empirical value. Steven Loyal expertly situates Bourdieu's work within the context of both classical and modern theories of the state, providing a comprehensive frame of reference. Finally, Loyal discusses Bourdieu's theoretical limitations and projects how his theory of the state might be utilized in the future. Steven Loyal is Associate Professor at the School of Sociology at University College Dublin, Ireland. His areas of interest include sociological theory, migration, the sociology of knowledge, social stratification, and historical sociology. .
Keywords: Social sciences.; Creative writing.; Social structure.; Social inequality.; Sociology.; Political sociology.; elektronické knihy; electronic books